Usability of Robinia pseudoacacia in monitoring changes and reducing airborne palladium pollution - Nazli AK TUTUNCU; Halil Baris OZEL; Hakan SEVIK; Hatice COBANOGLU (GSC Online Press, 2024)
Palladium (Pd), whose use has been increasing in recent years, is one of the heavy metals that pose a danger to the environment and human health, and it is known that heavy metals can be extremely harmful when inhaled from the air and taken into the human body. Therefore, monitoring and reducing the change of Pd pollution in the air is very important. This study aimed to determine the usability of Robinia pseudoacacia, which is grown intensively in urban areas where heavy metal pollution may be high, to monitor and reduce the change in Pd pollution in the air. Within the scope of the study, changes in Pd concentration in Robinia pseudoacacia stem sections grown in Düzce, among the 5 most polluted cities in Europe, depending on organ, direction, and age range in the last 60 years, were evaluated. As a result, it was determined that Pd pollution in the region may have been released into nature through agricultural activities or transported from much more distant sources. It was also determined that the species is not a suitable biomonitor that can be used to monitor the change in Pd pollution. Still, it is an accumulator species that is extremely suitable for reducing Pd pollution.
Keywords: Accumulator; Heavy metal; Robinia pseudoacacia; Biomonitor; Palladium